Iran’s High School English Textbooks (Vision Series) and Organizational Knowledge as a Component of CLT Model - Jamshidian , Fateme; Tabatabaei, Omid; Salehi , Hadi; Vahid Dastjerdi, Hossein (Journal of Critical Studies in Language and Literature, 2024)
Selecting an appropriate textbook is one of the key factors in teaching English. This content analysis study scrutinized whether organizational knowledge represented in Iranian high school English textbooks (Vision Series). Thus, the stance of organizational components as one of the Communicative Language Teaching (CLT) principles was investigated in such textbooks. George (1963) verb form frequency count, Halliday and Hassan’s (1976) model, McCrimman’s (1984) model, Vocabulary List Cambridge English (2012) were used to examine the extent to which organizational knowledge was shown in high school EFL textbooks. The analysis of the results revealed that grammatical knowledge was not presented comprehensively. Therefore, high school students would not be able to exhibit a wide variety range of vocabulary. Because the vision series roughly represented the sufficient vocabulary size. The Vision series highlighted intonation rather than pronunciation. The role of rhetorical organizations was disregarded in the Vision series. Therefore, he Vision series should be revised to include the organizational components. Generally, the Vision series did not follow CLT principles to promote language learners’ ability to communicate.